2018
DOI: 10.1039/c7ce02034a
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Insight into the reversible structural crystalline-state transformation from MIL-53(Al) to MIL-68(Al)

Abstract: The reversible crystalline transformation from MIL-53(Al) into MIL-68(Al) was accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The morphological transformation, from hexagonal needle shape to rhombic block shape, can be clearly observed in the corresponding SEM images (figure 2a,b). The analogous crystalline-state transformation between MIL-53(Al) and MIL-68(Al) was reported by Perea-Cachero and co-workers [20]. The transformation mechanism is regarded as the exchange or removal of guest molecules from the pores.…”
Section: Structure Transformation Analysissupporting
confidence: 73%
See 2 more Smart Citations
“…The morphological transformation, from hexagonal needle shape to rhombic block shape, can be clearly observed in the corresponding SEM images (figure 2a,b). The analogous crystalline-state transformation between MIL-53(Al) and MIL-68(Al) was reported by Perea-Cachero and co-workers [20]. The transformation mechanism is regarded as the exchange or removal of guest molecules from the pores.…”
Section: Structure Transformation Analysissupporting
confidence: 73%
“…units) intensity (arb. units) 20 30 analogous structural transformation from MIL-68(In) to QMOF-2, and verified that MIL-68(In) is an initial kinetic product and QMOF-2 is a final thermodynamic product of In 3þ with an excess amount of H 2 BDC [25]. To verify the tenability of this conclusion in In 3þ and H 2 BDC_NH 2 system, the amount of the ligand was continuously increased to M : L ¼ 1 : 6, and the reaction time was prolonged to 24 h. The PXRD result validates that exclusive QMOF-2 is formed.…”
Section: Structure Transformation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, coordination polymers and metal‐organic supramolecular compounds have gained tremendous attention not only for their fascinating structures and new topological prototypes, but also for their potential applications as functional materials in photoluminescence, adsorption, separation, ion exchange, magnetism and catalysis . To date, a large number of metal‐organic compounds with various architectures and good properties have been afforded based on the self‐assembly of appropriate metal ions and organic ligands .…”
Section: Crystallographic Data and Refinement Parameter Formentioning
confidence: 99%
“…Work by Wright et al demonstrated the possibility to prepare Sc 3+ analogues, of Al‐MOFs in terms of reticular chemistry (e.g. MIL‐53, MIL‐68, MIL‐100, and MIL‐101 (M = Al, Sc)). In particular Al‐MIL‐53, which is built up from trans ‐corner sharing AlO 6 polyhedra connected to four adjacent chains by the linker molecules, has been intensively studied due to the breathing behavior and the associated changes in the pores sizes upon exchange or removal of guest molecules.…”
Section: Introductionmentioning
confidence: 99%